2011
DOI: 10.1039/c1cp00052g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface chemistry and protein concentration on the adsorption rate and S-layer crystal formation

Abstract: Bacterial crystalline surface layers (S-layers) are the outermost envelope of prokaryotic organisms representing the simplest biological membranes developed during evolution. In this context, the bacterial protein SbpA has already shown its intrinsic ability to reassemble on different substrates forming protein crystals of square lattice symmetry. In this work, we present the interaction between the bacterial protein SbpA and five self-assembled monolayers carrying methyl (CH(3)), hydroxyl (OH), carboxylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
2
18
0
9
Order By: Relevance
“…However, because of the lack of resemblance to the natural case (in bacteria), these results were not considered for further comparison. However, similar results to those of the hydrophobic substrate in terms of frequency variation, as well as the presence of the structural transition peak in Δ D , have already been reported in previous studies as developed by our group for different types of hydrophobic alkylsilanes (octadecyltrichlorosilane) [17] and alkylthiols (dodecanethiol and hexanethiol) [18] on silica and gold, respectively. In those cases the real-time analysis differed significantly from the one carried out here.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, because of the lack of resemblance to the natural case (in bacteria), these results were not considered for further comparison. However, similar results to those of the hydrophobic substrate in terms of frequency variation, as well as the presence of the structural transition peak in Δ D , have already been reported in previous studies as developed by our group for different types of hydrophobic alkylsilanes (octadecyltrichlorosilane) [17] and alkylthiols (dodecanethiol and hexanethiol) [18] on silica and gold, respectively. In those cases the real-time analysis differed significantly from the one carried out here.…”
Section: Resultssupporting
confidence: 84%
“…In this regard, the quartz crystal microbalance with dissipation monitoring (QCM-D) has proven to be a powerful technique to follow in situ the binding of S-layers on different supports [1718]. The QCM-D responses, i.e., the resonance frequency f and the energy dissipation D of the shear oscillatory motion of a piezoelectric quartz crystal sensor, change upon adsorption or desorption of material on the surface of that sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In another set of experiments [69] the reassembly of the S-layer protein SbpA, again using AFM and QCM-D, was studied on different self-assembled monolayers carrying methyl (CH 3 ), hydroxyl (OH), carboxylic acid (COOH), and mannose (C 6 H 12 O 6 ) as terminating functional groups. It was found that the protein adsorption rate and the size of the crystalline domains were influenced by the introduced surface chemistry and protein concentration.…”
Section: Reassembly Of S-layer Proteinsmentioning
confidence: 99%
“…[32][33][34][35] Differential scanning calorimetry (DSC) was carried out to determine the glass transition, crystallization and melting temperatures of the polymers. Finally Tensile tests were performed to evaluate the Young's modulus (E), stress and strain at yield (σ y , ε y ), and stress and strain at break (σ b , ε b ) of the polymers.…”
Section: Introdutionmentioning
confidence: 99%